RELEVANSI ILMU TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SMA NEGERI 3 MERANGIN - Herpinah Imel Eka Mulyani; Rahmayanti Chaidir; Osna Yenti; Iskandar; Retno Wahyu Ningsih; Saukani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the relevance of scientific knowledge to improving the quality of education at SMA Negeri 3 Merangin, Merangin Regency, Jambi Province. Educational quality is a central concern in the national education system, where the application of relevant and current knowledge plays a decisive role in determining learning outcomes. The rapid development of science and technology demands that educational institutions continuously align their curriculum, teaching methods, and teacher competencies with the latest scientific advancements. This research employs a qualitative descriptive approach, with data collected through structured observation, in-depth interviews, and documentation analysis. The research subjects include the principal, eight teachers from various subject areas, and twenty students from grades X through XII. The conclusion is that systematic integration of relevant and up-to-date scientific knowledge into educational processes is essential for achieving higher standards of educational quality at SMA Negeri 3 Merangin, and requires coordinated support from all stakeholders including local government, education authorities, school management, and the academic community.